Rancang Bangun Alat Pemantau Kualitas Air Danau Berbasis Internet of Things Di Kantor DPRD Provinsi Kepulauan Riau - Soleh Vudin Gozali; Suhendra, Tonny; Hekso Yunianto, Anton (Sustainable, 2023)
When consuming lake water for sanitation purposes, information about the quality of the lake water consumed is needed or not. The design and manufacture of this lake water quality monitoring device aims to provide information on the feasibility of lake water used for sanitation purposes. This tool uses the parameters of temperature, pH, TDS and turbidity level. This water quality monitoring device uses ESP 32 as its microcontroller by using a temperature sensor, pH sensor, TDS sensor and water turbidity sensor. The results of measuring lake water quality will later be displayed on the OLED screen and also displayed on the Blynk android application.